2021
DOI: 10.3390/ph14111138
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Potential of Essential Oils against SARS-CoV-2 from In Silico Studies through the Systematic Review Using a Chemometric Approach

Abstract: Essential oils (EOs) and their compounds have attracted particular attention for their reported beneficial properties, especially their antiviral potential. However, data regarding their anti-SARS-CoV-2 potential are scarce in the literature. Thus, this study aimed to identify the most promising EO compounds against SARS-CoV-2 based on their physicochemical, pharmacokinetic, and toxicity properties. A systematic literature search retrieved 1669 articles; 40 met the eligibility criteria, and 35 were eligible fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 121 publications
0
26
0
Order By: Relevance
“…Previous in silico studies showed that the monoterpenes used in this study and other common essential oil constituents can bind and interfere with the function of viral proteins including main protease, endoribonuclease, ADP ribose phosphatase, RNA-dependent RNA polymerase, and spike protein, and human proteins important for viral life cycle including angiotensin-converting enzyme ( Silva et al, 2020 ; Torres Neto et al, 2021 ). Reported docking values of monoterpenes ( Silva et al, 2020 ) used in this study for binding the aforementioned protein targets are in the agreement with their antiviral activity against SARS-CoV-2 ( Table 2 ) with one exception as their results suggest that limonene should have the best antiviral activity, which, is not the case in our study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous in silico studies showed that the monoterpenes used in this study and other common essential oil constituents can bind and interfere with the function of viral proteins including main protease, endoribonuclease, ADP ribose phosphatase, RNA-dependent RNA polymerase, and spike protein, and human proteins important for viral life cycle including angiotensin-converting enzyme ( Silva et al, 2020 ; Torres Neto et al, 2021 ). Reported docking values of monoterpenes ( Silva et al, 2020 ) used in this study for binding the aforementioned protein targets are in the agreement with their antiviral activity against SARS-CoV-2 ( Table 2 ) with one exception as their results suggest that limonene should have the best antiviral activity, which, is not the case in our study.…”
Section: Discussionmentioning
confidence: 98%
“…Some essential oils are very active against human herpesvirus (HSV), influenza A virus (H1N1), avian influenza A virus (H5N1), and human immunodeficiency virus (HIV) ( Das et al, 2021 ; Wani et al, 2021 ). Furthermore, both essential oils and their monoterpene components might also have antiviral activity against SARS-CoV-2 as the molecular docking studies showed that different plant monoterpenes and sesquiterpenes might bind and interfere with the functions of different proteins of SARS-Cov-2 virus including main protease, endoribonuclease, ADP ribose phosphatase, RNA-dependent RNA polymerase and spike protein ( Silva et al, 2020 ; Das et al, 2021 ; Kim, 2021 ), and human cell proteins important for viral internalization and replication including, angiotensin-converting enzyme and cellular proteases, transmembrane serine protease 2, cathepsin B, and cathepsin L ( Silva et al, 2020 ; Panikar et al, 2021 ; Salem and Ezzat, 2021 ; Torres Neto et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, garlic EOs and their isolated constituents, particularly diallyl sulphide and allyl trisulphide, lemon and geranium EOs and their derivative compounds exemplify potential natural antiviral agents, which hinder coronavirus entry into the human body [ 41 ]. Various plants have been proposed as potential sources for anti-SARS-CoV-2 EOs, including Eugenia brasiliensis , Melissa officinalis , Cedrus libani , Zingiber zerumbet , Zataria multiflora and Vetiveria zizanoides [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Essential oils (EOs) are rich in a broad biological spectrum of compounds such as sesquiterpenes, monoterpenes, aldehydes, alcohols, esters, ketones, polyphenols, and flavonoids, including other classes, which result in a broad biological activity including antimicrobial, antifungal, insecticide, anti-inflammatory, antioxidant, anticarcinogenic, and antiviral [ 12 , 13 ]. Therefore, these oils have been successfully applied in different industrial sectors such as food, cosmetic, pharmaceutical, and agricultural industries [ 14 ].…”
Section: Introductionmentioning
confidence: 99%